Nutritional Status For Increasing Performance - Pipit Pitriani; Basiran Basiran; Nida'ul Hidayah (Jurnal Humanities Pengabdian Kepada Masyarakat, 2021)
Nutritional status in athletes is one of the important factors that affect athlete performance. Athlete's knowledge of nutrition is still lacking. Malnutrition and other health problems are found many in athletes. The purpose of this activity is trained athletes to improve the understanding of nutritional status and measure anthropometry to improve performance. This training contains materials that is needed to improve athlete's knowledge on nutritional status and anthropometric measurements. Further it can be used in the training process or in match conditions. This community service activity was attended by 29 participants consisting of female and male athletes as well as handball trainers. The activity is carried out online. Before and after the training participants fill out a google form for data on body weight, height, and questions about training materials. From the results of data processing, the average height for male athletes was 176 ± 6.33cm and for female athletes 164 ± 5.79cm. Meanwhile, the body weight of female athletes is 60.5 ± 8.3kg and male athletes are 74.02 ± 9.05kg. BMI in female athletes is 22.5 ± 2.2kg / m2 and in male athletes 23.88 ± 1.88 kg / m2. The mean pre-test score for female athletes was 60.35 ± 11.09, while for male athletes it was 60.35 ± 14.69. The average post-test score for female athletes was 67.85 ± 11.90, while for male athletes the average post-test score was 72.5 ± 9.20. Thus, the difference (gain) change in post-test scores to pre-test in female athletes is 12.43% and 20.12% in men. From this training, it can be concluded that there is an increase in the knowledge of handball athletes regarding nutritional status, nutrition, and dietary regulation in athletes. It is hoped that further this community service activity can be carried out in terms of determining the calorie and nutritional needs of athletes as well as athletes can be given knowledge about how to make food menus according to the needs of athletes.